Improving Curriculum Organization In The Education System In School - Rosena Maulida (Indonesian Journal of Education (INJOE), 2021)
The world of education cannot be separated from the curriculum. The curriculum is one of the most important components of education. The curriculum can cover a broad scope and a narrow scope. The curriculum must be in accordance with the needs and demands that exist in society. The curriculum must also be able to adjust the components in it. In its implementation in an educational institution, the curriculum needs to be developed, in developing a curriculum it certainly cannot be done without references or guidelines. One of the curriculum developed must pay attention to curriculum organization. Organizing the curriculum is one aspect that needs to be considered so that curriculum development can meet all the needs and demands of students, educators, and also the community. This study uses the Library Research method by examining several data sources from books related to the organization and design of curriculum development. The conclusion of this study is that the organization acts as a method used to determine the selection and integration of various learning experiences organized by educational institutions in the curriculum development process. An organization is very necessary for the management process, namely the planning organization, the organization in the context of implementing the curriculum, and the organization in the context of curriculum evaluation.